THE INFLUENCE OF FINANCIAL KNOWLEDGE, FINANCIAL CONFIDENCE, AND INCOME ON FINANCIAL BEHAVIOR AMONG THE WORKFORCE IN JAKARTA - Agus Zainul Arifin; Kevin Kevin; Halim Putera Siswanto (MIX: JURNAL ILMIAH MANAJEMEN, 2017)
Abstract. The purpose of this study is to analyze the influence of financial knowledge,financial confidence and income, on financial behavior. This research is based onTPB Model and Behavioral Finance Theory, and it was carried out based on thephenomenon that occur at present whereas the community is more focused on shorttermrather than on long-term. The Theory of Planned Behavior that rates theknowledge, self-confidence, and income becomes the basis of financial behavior ofindividuals, which become the topic of this research. The subjects in this study are thepeople of Jakarta Special Region, which includes the group of workforce who havealready had the job and fixed income every month. The results of this research showthat Financial Knowledge and Financial Confidence do affect Financial Behavior,whereas Income does not appear in the same way.Keywords: Financial Behavior, Financial Knowledge, Financial Confidence, Income